Editorial Note: Uji Validitas Dengan Korelasi Item-Total ? - Hendryadi Hendryadi (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
Editorial Note: Statistical techniques to test the validity, especially those from questionnaires, can use three approaches: the SEM approach, single-factor analysis (EFA and CFA), and Multitrait-Multimethod (MT-MM) to test convergent validity and discriminant validity, and confirmatory component analysis. (CCA) which uses the SEM-PLS approach.